The Influence of Islamic Social Reporting and Islamic Corporate Governance on Financial Performance in Islamic Banking in Indonesia - Adib Asyraf; Afrizal Afrizal; Muhammad Ridwan (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to determine the influence of Islamic Social Reporting and Islamic Corporate Governance partially and simultaneously on financial performance. The population of this study is Islamic Banking companies registered with the Financial Services Authority in 2019 - 2023. Sampling was carried out using the purposive sampling method, namely the sample was selected using certain considerations according to the established criteria. The sample selected in this study was Islamic Banking Companies registered with the Financial Services Authority, did not carry out mergers, acquisitions or spin-offs with other Islamic Banking companies, and had annual reports, and GCG implementation reports consistently and completely from 2019 - 2023. Data analysis in this study used multiple regression analysis. The results of this study indicate that Islamic Social Reporting partially has a significant influence on financial performance, while Islamic Corporate Governance partially does not have a significant effect on financial performance. The results of simultaneous testing indicate that Islamic Social Reporting and Islamic Corporate Governance together have a significant effect on the financial performance of Islamic Banking in Indonesia.